The level of household satisfaction with community-based health insurance and associated factors in Southern Ethiopia - Zepre, Kebebush (Frontiers in Public Health, 2023)
Background: Community-based health insurance (CBHI) scheme is an emerging strategy for providing financial protection against healthcare-related poverty. In Ethiopia, CBHI is being implemented in all the regions, but community experience and satisfaction with the scheme have not yet to be studied. Objective: This study is aimed to assess the magnitude of household’s satisfaction on community-based health insurance schemes and associated factors in Southern Ethiopia. Methods: A community-based cross-sectional study was conducted for 528 household in gurage zone, southern Ethiopia, from April to May 2021. Data were collected on 528 households by using simple random sampling method. Trained data collectors gathered the data using a pre-tested and structured questionnaire. Descriptive statistics, bivariate and multivariable logistic regression analyses were performed. To determine the independent predictors of household’s satisfaction to CBHI, a cut point of p values < 0.05 were used. Results: The magnitude of households’ satisfaction was 54.2%, highest wealth status (adjusted odds ratio [AOR] = 2.36, 95% confidence interval [CI]:1.14–4.87), good knowledge of CBHI (AOR: 1.81, 95% CI: 1.87–3.37), illness experienced in the last 3 months (AOR: 5.21, 95% CI: 2.90–9.33). frequent health facility visits (AOR:5.03, 95% CI:1.17–23.43), graduated in the model household (AOR: 3.20, 95% CI:1.75–5.83), enrolled in the CBHI for more than 3 years (AOR:0.55, 95% CI: 0.29–0.94), trusting governing bodies (AOR:10.52, 95% CI:4.70–23.53) and the prescribed drug available in the contractual facility (AOR:14.62, 95% CI:5.37–39.83) were significant influencing factors of the magnitude of household s satisfaction with community-based health insurance. This study findings revealed various factors which influenced households satisfaction to CBHI: wealth status, HHs knowledge of CBHI, illness experience in the household, the familiarity of HHS to health facility visits, graduated in model household , trust on CBHI governing board , getting the prescribed drug in the contractual health facility, and length of time enrolled in CBHI program. We powerfully recommend all responsible stakeholders give strong attention to enhancing HHS knowledge of CBHI scheme, support households to be model in rural health extension package and fulfilling the pledged package of CBHI in order to improve HHS satisfaction to CBHI scheme